HDL attenuates Ang II–AT1R–EGFR signaling and reverses vascular remodeling in spontaneously hypertensive rats - Al-Jarallah, Aishah; Kalakh, Samah; Akhtar, Saghir; Yousif, Mariam H. M. (Frontiers in Pharmacology, 2025)
BackgroundAngiotensin II (Ang II) signaling via angiotensin II type 1 receptor (AT1R) and transactivation of epidermal growth factor receptor (EGFR) enhances vascular smooth muscle cell (VSMC) proliferation and contributes to vascular remodeling evident in spontaneously hypertensive rats (SHR) aorta. Although high-density lipoprotein (HDL) has been shown to lower blood pressure in SHR, the underlying mechanism(s) remain incompletely understood. We propose that HDL attenuates Ang II–AT1R–EGFR signaling and reverses vascular remodeling in SHR.MethodsWistar Kyoto rats (WKY) and SHR were treated with HDL for 1 week. Vascular remodeling was histologically examined. VSMC proliferation and the expression levels of AT1R, EGFR, extracellular signal regulated kinases 1/2 (ERK1/2), scavenger receptor class B type-I (SR-BI) and its adaptor protein PDZK1 were examined by immunofluorescence. VSMC proliferation was further examined in vitro.ResultsHDL treatment reduced blood pressure, increased the production of nitric oxide, increased aortic lumen diameter, reduced media thickness to lumen diameter ratio, decreased collagen contents in SHR. Furthermore, HDL treatment decreased the number of proliferating VSMCs and α-smooth muscle actin, reduced the expression of AT1R and EGFR and increased the expression of SR-BI adaptor protein, PDZK1, in SHR aortas. In isolated VSMCs, HDL attenuated Ang II-induced proliferation by reducing AT1R expression and decreasing Ang II-induced transactivation of EGFR. HDL effects were SR-BI dependent and were mimicked by different HDL subpopulations, reconstituted HDL, and lipid free apolipoprotein A-I.ConclusionHDL attenuates Ang II–AT1R–EGFR signaling, reduces VSMC proliferation, and reverses vascular remodeling in SHR. HDL modulation of vascular remodeling could be one mechanism by which HDL reduces blood pressure in SHR.